1987
DOI: 10.1172/jci113172
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of phosphorus modulates the circadian rhythm in serum concentration of phosphorus. Implications for the renal production of 1,25-dihydroxyvitamin D.

Abstract: IntroductionWe recently reported that in healthy men, changes in the production rate (PR) (29), the serum concentration of 1,2540H)2D decreases. We have shown in healthy men that these phosphorus-induced changes in serum concentration of 1,25-(OH)2D can be accounted for entirely by changes in the production rate (PR) of the hormone (25). The mechanism by which changes in dietary phosphorus induce changes in the PR of 1,25-(OH)2D has, however, not been defined. In the chick and rat, the concentration ofphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
132
2
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(150 citation statements)
references
References 48 publications
14
132
2
2
Order By: Relevance
“…In normal, healthy men given phosphorus-supplemented diets, single, fasting morning serum phosphorus concentrations grossly underestimate 24-hour exposure to phosphorus and fail to distinguish between low and high dietary phosphorus intake. 18 Our results suggest that, in moderate to advanced CKD, the serum phosphorus concentration may be a relatively poor marker of phosphate binder efficacy or adherence.…”
Section: Discussionmentioning
confidence: 71%
“…In normal, healthy men given phosphorus-supplemented diets, single, fasting morning serum phosphorus concentrations grossly underestimate 24-hour exposure to phosphorus and fail to distinguish between low and high dietary phosphorus intake. 18 Our results suggest that, in moderate to advanced CKD, the serum phosphorus concentration may be a relatively poor marker of phosphate binder efficacy or adherence.…”
Section: Discussionmentioning
confidence: 71%
“…Figure 4 illustrates how both serum phosphate and PTH fluctuate with an inherent biphasic pattern, peaking in the afternoon and late evening but readjusting to the morning fasting concentration of the previous day (indicated by the arrows). This phenomenon of readjusting to the morning fasting concentration of the previous day has been shown for serum phosphate (16,(42)(43)(44), PTH (16,43), and, although less convincingly, FGF-23 (41,45). The need for multiple serum sampling to monitor dietary phosphorus effects on calcium and phosphorus balance was first suggested by Smith and Nordin in 1964 (42), when they were unable to demonstrate a change in serum calcium or phosphate concentrations in response to phosphorus intake using a single daily blood sampling.…”
Section: Masking Of Diet-related Changes In Serum Phosphorus Pth Anmentioning
confidence: 66%
“…Sampling during usual morning hours when study participants are in a fasted state, as is commonly done, will impair the ability to determine associations between dietary intake, phosphaturic hormones, and cardiovascular, renal, or skeletal disease biomarkers (16,34,(41)(42)(43)(44).…”
Section: Masking Of Diet-related Changes In Serum Phosphorus Pth Anmentioning
confidence: 99%
“…Previous studies have demonstrated that, in order to counteract hyperphosphataemia, bioactive parathyroid hormone secretion is raised (Table 5; Reiss et al, 1970;Silverberg et al, 1986). However, hyperphosphatemia, induced by a high phosphorus intake, is associated with a decrease of 1,25-(OH) 2 D 3 concentration in the serum (Lobaugh, 1995;Portale et al, 1987). Contrary to this, Silverberg et al (1986) noticed no changes in 1,25-(OH) 2 D 3 concentrations (Table 5).…”
Section: Discussionmentioning
confidence: 90%